2018
DOI: 10.3390/su10030632
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Psychometric Properties of Perceived Motivational Climate in Sport Questionnaire and Its Relationship to Physical Activity and Gender Using Structural Equation Modelling

Abstract: (1) Background: Different authors have established that each type of motivation to sports can favor healthy habits in men and women, being important to promote more self-determined motivations. (2) Methods: The present study was designed to assess selected psychometric properties of the Perceived Motivational Climate in Sport Questionnaire and study the relationship between motivational climate, physical activity and gender in adolescents. Research was conducted with a sample of 2134 Spanish children (12.5 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…The second instrument was the perceived motivational climate in sport questionnaire (PMCSQ-2, [34,35]). This scale allows to establish two dimensions of motivational climate in sport through 33 items scored, using a five-point Likert-scale where 1 = Strongly Disagree and 5 = Strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…The second instrument was the perceived motivational climate in sport questionnaire (PMCSQ-2, [34,35]). This scale allows to establish two dimensions of motivational climate in sport through 33 items scored, using a five-point Likert-scale where 1 = Strongly Disagree and 5 = Strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is no consensus in the literature regarding the effects of gender and age on different variables linked to sporting activity (e.g. Conaway and Cort es-Garay, 2014;Greenwell et al, 2015;Hazari, 2018;Janssen et al, 2017;Molanorouzi et al, 2015;Zurita-Ortega et al, 2018).…”
Section: 3mentioning
confidence: 99%
“…10% of all deaths each year) and 8.3 million disabilities are caused by a lack of physical activity [1]. Ortega et al [2] suggested that physical education in early life-stage plays an important role in promoting physical activity and healthy lifestyle behaviours throughout adulthood. Regular physical activity every week reduces the risk of diabetes, coronary heart disease, hypertension, depression, and breast and colon cancer, and increases life expectancy [3], ensures mental wellbeing, and helps to prevent osteoporosis and to maintain viability in older people [4].…”
Section: Introductionmentioning
confidence: 99%